Transcriptomic and functional analysis of EWSR1-CREM fusion oncogene in melanoma cell line CHL-1 - Saustila, Lotta (My University, 2022)
Fusion genes bearing EWSR1-CREB have been reported in several neoplasms of variating origin, also in melanoma. However, not many have concentrated on the functional role of EWSR1-CREB family fusions in vitro. Less studied fusion EWSR1-CREM has an estimated prevalence of 0,5% - affecting nearly 10 000 new patients per year. It has been shown that knockdown of this fusion on melanoma cell line CHL-1 with the 3’ end of CREM-targeting siRNA reduces proliferation and invasion and induces cell senescence. Our study aimed to verify the hypothesis of EWSR1-CREM’s pro-oncogenic nature and study EWSR1-CREM protein’s target genes. To induce EWSR1-CREM knockdown, CHL-1 cells were treated with 3’ end CREM-targeting siRNA pool. Knockdown was validated using RT-PCR. Cell studies were made to examine the hallmarks of cancer. Pathway analysis was performed to identify EWSR1-CREM mediated pathways. FACS was used to analyze cell cycle alterations. Our study showed that EWSR1-CREM is an oncogenic fusion and knockdown of wild type CREM had only little effect on cell phenotype. EWSR1-CREM knockdown altered expression of 712 genes affecting mainly cell cycle, proliferation, and apoptosis. One of those genes was ODC1, a known oncogene and polyamine synthesis mediator. Our study showed that oncogenic properties of EWSR1-CREM are largely mediated through the altered expression of ODC1. Further studies are needed to explore if EWSR1-CREM bearing tumors in general overexpress ODC1 and the possibilities of CREM-ODC1 axis targeted treatment.
Keywords: fusion gene, melanoma, EWSR1-CREM, ODC1